The prevalence of pelvic organ prolapse and associated factors in Ethiopia: a systematic review and meta-analysis - Addisu, Dagne; Mekie, Maru; Belachew, Yismaw Yimam; Degu, Alemu; Gebeyehu, Natnael Atnafu (Frontiers in Medicine, 2023)
Background Pelvic organ prolapse (POP) affects millions of women globally, with resource-limited countries, such as Ethiopia, carrying the highest burden. Previously, the prevalence of POP was estimated using seven studies. However, this study lacks generalization because of the limited number of studies and low geographical representation. In total, 12 additional primary studies were conducted after this review, and their reported prevalence was significantly variable across the studies. In addition, different new factors were reported in the primary studies. Therefore, this study aimed to update the pooled prevalence of POP and its associated factors in Ethiopia. Methods This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Articles that were published between 2000 and 2023 were searched using the African Journal of Online, ScienceDirect, DOAJ, PubMed, and Google Scholar. The quality of the studies was evaluated using the modified Newcastle-Ottawa quality assessment tool. The data were extracted using Microsoft Excel and analyzed by Stata version 11. A random effect model was used to investigate the pooled prevalence of POP and its associated factors. The I2 test and Egger's regression test were used to detect the presence of heterogeneity and publication bias across studies, respectively. Result A total of 21 studies met the inclusion criteria and represented the data of 14,575 women. The pooled prevalence of POP was found to be 22.70%. History of home delivery (pooled odds ratio (OR) =2.93, 95% CI =1.46, 5.91), prolonged labor (OR = 4.63, 95% CI = 2.56, 8.38), history of perineal tear (OR = 4.83, 95% CI = 2.31, 10.11), instrumental delivery (OR =3.70, 95% CI =2.01, 6.81), grand multipara (OR = 5.42, 95% CI = 4.06, 7.23), family history of POP (OR = 3.30, 95% CI = 2.07, 5.25), and carrying heavy objects (OR = 3.23, 95% CI = 2.22, 4.70) were significantly associated with POP. Conclusion The pooled prevalence of POP was high in Ethiopia. The Ministry of Health and clinicians should emphasize counseling on modifiable risk factors and develop further prevention strategies.